Contour 2003 : een wandeling langs hedendaags bewegend beeld (Mechelen : Contour, 2003)
Tan, Fiona; Op De Beeck, Hans; De Rijke, Jeroen; De Rooij, Willem; Wauman, Wim; Lambrechts, Franciska; Honoré d'o; Barry, Orla; Chafes, Rui; Messieurs Delmotte; Augustijnen, Sven; Dietvorst, Els; Johannesma, Rob; Neus, Elske; Geys, Jef
Publicatie n.a.v. "Contour" te Mechelen, 15.08.2003 - 12.10.2003
boek